(untitled) (Journal of actual problems of jurisprudence, 2025)
The contract for the provision of services in the digital economy is a crucial legal instrument that governs the interaction between entities in rapidly evolving digital ecosystems. Digitalization is transforming traditional legal relationships, necessitating the adaptation of regulations and the development of new methods for regulating transactions in a digital environment. This study focuses on the specific aspects of entering into and executing service agreements in a digital setting, including their electronic format, automating processes for agreeing on terms, and implementing smart contracts. The study examines the specific legal aspects of these agreements, including issues of consumer protection, cybersecurity, data processing and transfer, and the complexities of jurisdiction in cross-border transactions. It also addresses the challenges of legally identifying the parties involved, proving the expression of their will, and ensuring compliance with obligations in virtual environments. The article emphasizes the significance of enhancing legislation and harmonizing legal standards at the international level in order to guarantee legal certainty and safeguard participants in digital transactions. Furthermore, the research paper proposes potential strategies for establishing a flexible and long-lasting legal framework for service agreements in the digital economy. Keywords: service agreement, digital economy, smart contracts, electronic transactions, cybersecurity, international law.